Am I Expected to Be Ethical? A Role-Definition Perspective of Ethical Leadership and Unethical Behavior - Paterson, Ted A.; Huang, Lei (Journal of Management, 2019)
Prior studies have demonstrated that leaders’ ethical behaviors have an impact on followers’ unethical behaviors, and yet the explanatory mechanisms in this relationship have not been fully explored. To further explicate the relationship between ethical leadership and unethical employee behavior, we adopted a role-based perspective and introduced the concept of role ethicality. That is, we explored the impact that leaders’ actions and voice behaviors, particularly regarding ethical issues, have on perceptions of ethical role requirements and in turn the effect such perceptions have on unethical behavior. In a field study involving 394 employees and 68 supervisors and a randomized experiment conducted with 121 working professionals, we find that as predicted, leaders’ behaviors and ethical voice have a significant influence on role ethicality, which in turn impacts unethical behavior. Based on our empirical findings, we describe the implications, limitations, and future directions relevant to this study.